Las tribus juveniles en tiempos de la modernidad - Rossana Reguillo (Estudios sobre las Culturas Contemporáneas)
In this text, the author discusses the ways in which adolescents formgroups and also enquires about the rooted local practices that incor-porate both national and transnational dimensions. Itfurther moreoffers a series of elements that today characterize adolescent culturesand how these make up a permanent present, integrate the changes,contradictions and displacements broughton by modernity.